Identifying and quantifying the degradation efficiency of chitinase in _Pseudomonas_ - Vlasak, Isabela Marie (Jihočeská univerzita, 2023)
This thesis investigated the viability of employing chitinase from Pseudomonas bacteria produced in bioreactors as a potential solution to control fungal crop diseases in order to minimize the demand for harmful synthetic pesticides in agriculture. Significant works related to the research were collated, providing an extensive literature review. A chitinase assay kit and fluorescent plate reader were used to analyze the efficiency of bacterial chitinase in degrading chitin from different sources and recorded fluorescent readings corresponding to endochitinase and exochitinase were quantified.
Identifying and quantifying the degradation efficiency of chitinase in _Pseudomonas_
Keywords: _Pseudomonas_; phytopathogens; biofungicides; chitin; endochitinase; exochitinase; fluorometric assay; enzyme quantification; _Pseudomonas_; phytopathogens; biofungicides; chitin; endochitinase; exochitinase; fluorometric assay; enzyme quantification